(untitled) (Clinics, 2021)
Our systematic review evaluates surgically relevant information about corona mortis (CM), such as anatomical structure, size, laterality, incidence, and anthropometric correlations. This study aimed to provide data about anastomosis in an attempt to avoid iatrogenic damage during surgery. Articles were searched online using the descriptor ‘‘Corona Mortis’’ in PubMed, Biblioteca Virtual em Sau´ de (BVS) (Literatura Latino-Americana e do Caribe em Sau´ de [LILACS], MEDLINE, indice bibliografico espan˜ ol en ciencias de la salud [IBECS]), and SciELO database. The time range was set between 1995 and 2020. The articles were selected according to their titles and later the abstracts’ relation to our research purpose. All the selected articles were read entirely. A manual search based of the references cited in these articles was also conducted to identify other articles or books of interest. Forty references fulfilled the criteria for this review. The mean incidence of CM was 63% (the majority venous) among 3,107 hemipelvises. The incidence of bilateral CM was lower than that of unilateral variations based on the analysis of 831 pelvises. The mean caliber of the anastomosis was 2.8 mm among 1,608 hemipelvises. There is no consensus concerning the anthropometric influences in CM. Finally, we concluded that CM is not an unusual anatomical variation and that we must not underestimate the risk of encountering the anastomosis during surgery. Anatomical knowledge of CM is, therefore, essential in preventing accidents for surgeons who approach the inguinal and retropubic regions.